Thermoplastic electrode surface modifications for use as label-free electrochemical immunosensors - Martinez, Brandaise, author; Henry, Charles S., advisor; Reynolds, Melissa, committee member; Snow, Christopher, committee member; Tobet, Stuart, committee member (Colorado State University. Libraries, 2024)
Point-of-care (POC) testing has grown in popularity in recent years, though most common lateral flow assay (LFA) techniques lack sensitivity and are not quantitative. Electrochemical sensors are a promising alternative, specifically thermoplastic electrodes (TPEs) due to their electrochemical performance and durability while remaining inexpensive. TPEs have been used for a wide variety of applications, but their use as immunosensors has been limited due to difficulty with antibody immobilization. This work seeks to explore techniques for modifying TPE surfaces for use as label-free immunosensors. Chapter 2 examines common antibody immobilization techniques applied to TPEs and determines that the standard existing protocols are lacking. Passive adsorption, EDC/NHS coupling, and chitosan films are used to attach antibodies to the surface. It was found that while each are commonly used in immunosensor fabrication, they have drawbacks that make them unsuitable for TPE immunosensors. Passive adsorption results in unstable antibody attachments leading to inconsistent sensing. EDC/NHS crosslinking is prone to side reactions and again led to inconsistencies in detection of the antigen. Chitosan films were perhaps the most promising, but they passivated the electrode to the extent that detecting the antigen was limited. Chapter 3 moves towards the development and characterization of a new TPE surface modification using aryl diazonium grafting followed by click chemistry to biotinylate electrodes for easy antibody immobilization. A variety of electrochemical techniques and surface characterizations were used to examine the stepwise modification of the TPE surface. It was shown that click chemistry can be successfully used on TPEs to attach various moieties following aryl diazonium grafting. Ethynyl ferrocene was clicked to the surface resulting in a surface coverage (ΓFc) of (1.0 ± 0.2) × 10-10 mol∙cm-2, which is comparable to literature values for similar approaches on commercial carbon electrodes. Streptavidinated antibody was successfully attached as well with a clear change in electrochemical signal upon binding. The method is expanded in Chapter 4 with the use of heterogeneous modifications with multiple functions. The monolayer contains surface bound ferrocene to aid in electron transport, long polyethylene glycol (PEG) spacers to block nonspecific adsorption, in addition to the antibody immobilization point. The modified TPEs were used to successfully detect the nucleocapsid protein of inactivated SARS-CoV-2 virus in buffer solution as a proof-of-concept without the need for a label. The LOD was approximately 6 PFU/mL which exceeds many existing POC tests for COVID-19. The work here expands on the potential applications of TPEs with increased performance and durability over other carbon electrode immunosensors. Potential future directions to expand the sensing capabilities include multiplexed sensors, alternative electrode materials, and expanding to non-antibody based systems.